KAJIAN SEMIOTIK DALAM UNGKAPAN POLITIK MASYARAKAT JAWA DI KECAMATAN GEMOLONG - Wildan Sahidillah, Muhammad (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2020)
Language is an arbitrary sound-symbol system used for communication/interaction. Language is used as a communication tools in the political election. Political expression in the community of Jatibatur Village, contain signs that refer to certain things. The purpose of this study is to know: 1) political disclosure used people in Jatibatur Village, Gemolong Sub-district, and 2) the meaning of political disclosure used in Jatibatur Village, Gemolong Sub-district. The research method used in this research using an interview technique, see, and note. This study is descriptive qualitative research. The data analysis technique in this study is using the analysis of the sign by Charles Sanders Pierce. The result of this study are; 1) the existence of a Java lexicon, ?abang? refers to PDI Perjuangan party, 2) the existence of a Java lexicon ?wit ringin? refers to Golkar?s party in Indonesian, 3) the lexicon of a ?wong cilik? in Java language especially in political, is refers to a poor people ora middle or lower class of people, 4) ?ojo pedhot oyot? a tagline from PDI Perjuangan party in Centra Java, means to continue what was been fought, and 5) ?caleg kae dekengane akeh? had a meaning that he had strong protection.